Measurement of Tensile Properties and Hardness of Friction Stir Welded Aluminium Alloy AA1200. (2020) - George Joseph, Melbin; Shaji, Josemon; Francis, Mathew; Raghavan, Arjun; Shunmugesh, K.
Abstract: Friction Stir Welding is set apart from other fusion welding techniques because of its ability to produce very high-quality welds even in high strength aluminium alloys. The process forges the weld region locally to produce the joint and hence is solid state in nature as it does not involve full melting. In this experimental research work an investigation was carried out on Friction Stir welding butt joint, to study the changes in its micro hardness, yield strength and ultimate tensile strength. The welded joints were made on AA 1200 grade aluminium strips of 3 mm thickness with the help of H13-Tool Steel 56 HRC tool of two different pin profiles. Two different pin profiles viz. cylindrical with groove, and tapered were used to fabricate the joints at Three different tool rotational speeds and three different feed rates.